On Two rare Italian Palliduphantes species (Araneae: Linyphiidae) - Alessio Trotta; Robert Bosmans (Fragmenta entomologica, 2021)
Male and female sexes of Palliduphantes petruzzielloi are described from the Grotta Strazzatrippa in Campania, Italy. A new southernmost Italian locality of P. istrianus is given from Campania.